The order of consideration of special proceeding cases in civil process - Aliyeva, L.R.; Ilyassova, G.A. (KSU publ, 2015)
This article is devoted to the features of disposal of legal cases of special proceeding in civil procedural law. The basic problems arising by disposal of legal cases of special proceeding are considered. The authors analyze the operating civil legislation on special proceeding as one of kinds of civil legal proceedings. The authors investigate questions of the legal nature of special proceeding, a subject of judicial activity and the list of cases of special proceeding. The various theoretical positions about considered legal relations are exposed to the analysis also in this article.
Keywords: civil procedural law; special proceeding, civil procedural legislation; civil proceeding; legal facts; evidentiary facts; legal regulation; legal capacity; restoration of violated rights; notarial actions